2006
DOI: 10.1682/jrrd.2005.05.0080
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of linear polarized 0.6 to 1.6 um irradiation of lumbar sympathetic ganglia in chronic constriction injury rats

Abstract: Abstract-Linear polarized near-infrared light created with linear polarized near-infrared light therapy equipment (Super Lizer TM HA-550, Tokyo Iken Co, Ltd, Tokyo, Japan) has been used for the treatment of various painful disorders in Japan. Irradiation near the stellate ganglion with a Super Lizer (ISGL) is an especially notable therapeutic method used with stellate ganglion block (SGB) or substitutes for SGB. ISGL is a safe, simple, well-tolerated, and effective treatment. We examined the effects of irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Indeed, Kashima et al [3] observed changes in sensory and pain perception thresholds in the trigeminal region, and Muneshige et al [14] observed antinociceptive effects in vivo in rats after the treatment of LPNIR.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Kashima et al [3] observed changes in sensory and pain perception thresholds in the trigeminal region, and Muneshige et al [14] observed antinociceptive effects in vivo in rats after the treatment of LPNIR.…”
Section: Discussionmentioning
confidence: 99%
“…Polarized light applied to the skin over the trigeminal nerve (on the cheek) reduced pain sensitivity both on the treated skin and on the forearm [45], suggesting that the effects of photomodulation of one nerve can be transferred to other nearby neural pathways. Muneshige et al [61] used polarized near-infrared light (wavelength range 600-1600 nm) allied to the lumbar area of rats (n = 11) in a sciatic nerve ligation model. A single treatment of 60 s irradiation significantly reduced hyperalgesia for at least 8 h post-treatment, while daily application, beginning one week after nerve ligation significantly reduced hyperalgesia for up to one month (after which the non-irradiated controls were returning to normal.…”
Section: Photomodulationmentioning
confidence: 99%
“…The equipment required for LPNR irradiation is a phototherapy device that emits infrared rays at deep penetrating wavelengths (600–1,600 nm) 3 , 4 , 5 , 6 , 7 ) . LPNR irradiation is commonly used in various therapeutic scenarios because of its noninvasiveness, safety, and simplicity 2 , 4 , 5 , 6 , 8 , 9 , 10 ) .…”
Section: Introductionmentioning
confidence: 99%